"I'm Having a Little Struggle With This, Can You Help Me Out?": Examining Impacts and Processes of a Social Capital Intervention for First‐Generation College Students. Issue 1 (27th November 2017) - Schwartz, Sarah E. O.; Kanchewa, Stella S.; Rhodes, Jean E.; Gowdy, Grace; Stark, Abigail M.; Horn, John Paul; Parnes, McKenna; Spencer, Renée
Abstract: Social capital plays a key role in college and career success, and research indicates that a dearth of on‐campus connections contributes to challenges first‐generation college students face in effectively navigating the college environment. This study investigates a novel intervention that focuses on the development of skills and attitudes to empower first‐generation college students to cultivate social capital and on‐campus connections during the transition to college. A mixed methods, explanatory design was used to evaluate impacts and processes of the intervention among first‐generation college students ( n = 164) in the context of an ethnically diverse, urban, public university in the Northeast. Results indicated that students who participated in the intervention demonstrated improved attitudes and behaviors around seeking support in college, closer relationships with instructors, and higher GPAs at the end of their first year in college. These results suggest the potential benefits of a relatively scalable approach to supporting the needs of first‐generation college students. Highlights: Social capital plays a key role in college and career success. Social capital is unequally distributed during the transition to college. Workshops can change students' attitudes and behaviors related to the acquisition of social capital. A social capital workshop can improve first‐generation college students' academic outcomes.